Gradual increase of BR1M proves govt's concern for low-income group - New Sabah Times English, (KK) (New Sabah Times English (KK), 2013)
KUALA LUMPUR:The gradual increase of the 1Malaysia People's Aid (BR1M) up to RM1,200 to tackle cost of living as stated in the Barisan Nasional (BN) manifesto proves the government's concern towards the low income group.